Implementasi Kebijakan Pembebasan Bersyarat Narapidana Di Lembaga Permasyarakatan Kelas II A Kupang (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2025)
The research, titled "Implementation of the Parole Policy for Prisoners at the Class IIA Kupang Penitentiary," explores parole as an integral part of the correctional system, aiming to provide prisoners with a chance to reintegrate into society. This study analyzes the implementation of the parole policy at the Class IIA Kupang Penitentiary, focusing on the mechanisms, challenges, and the impacts on prisoners and the broader community. The research employs a qualitative approach, utilizing interviews, observations, and documentation studies to gather data. Findings show that the effectiveness of the policy implementation is influenced by several factors, including regulatory frameworks, the readiness of prisoners to reintegrate, and support from their families and local communities. Key challenges identified include limited resources, the social stigma faced by former prisoners, and the effectiveness of rehabilitation programs within the prison system. Despite these challenges, the study highlights the importance of collaboration between the government, prisons, and the community to ensure the successful social reintegration of parolees. It suggests that improving coordination and support structures will contribute to better outcomes for parolees, reducing recidivism rates, and fostering a more inclusive society. In conclusion, the research underscores the need for continued efforts to refine and implement effective parole policies to aid the rehabilitation process and support the broader goals of the correctional system.